Occurrence of polycyclic aromatic hydrocarbon metabolites in urine of Portuguese firefighters - K. Slezakova (2015)
The present work estimates occupational exposure of healthy and non-smoking Portuguese firefighters to polycyclic aromatic hydrocarbons (PAHs) through the analysis of four urinary metabolites (OH-PAHs): 1-hydroxyacenaphthene, 1-hydroxynaphthalene, 1-hydroxypyrene (PAH biomarker of exposure), and 3-hydroxybenzo[a]pyrene (PAH biomarker of carcinogenicity). Firemen from several Portuguese corporations were asked to provide urine samples during the winter period (without exposition to fires; pre-fire season) and during the summer season of 2014 after fires fighting. The selected OH-PAHs were extracted from urine samples by solid-phase extraction and analyzed by high-performance liquid chromatography with fluorescence detection. Normalization of the urinary PAH-metabolite levels was achieved by analyzing the creatinine concentrations. 1-hydroxynaphthalene and 1-hydroxyacenaphthene were the most abundant metabolites, followed by 1-hydroxypyrene. The metabolite 3- hydroxybenzo[a]pyrene was not detected. Total OH-PAHs ranged from 0.02 to 4.01 μmol/mol creatinine and between 0.55 to 8.39 μmol/mol creatinine, respectively, for non exposed and exposed firefighters. In general, the detected concentratio